Implementasi Pembiasaan Ibadah dan Keteladanan Guru dalam Meningkatkan Kecerdasan Emosional Anak Usia Dasar - Allifatur Rohma; Yanti Yuniarti; Neneng Nurhayati; Muhammad Alfi Syahrin (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
This study aims to describe the implementation of religious habituation practices and teacher role modeling, as well as to analyze the effects of both variables on the emotional intelligence of elementary school children. A quantitative approach with a correlational research design was employed. The study was conducted at SDN Bayeman I, involving a population of 93 students from grades IV, V, and VI, from which a sample of 76 students was selected using stratified random sampling techniques. The research instruments consisted of validated and reliable questionnaires measuring religious habituation, teacher role modeling, and emotional intelligence. Data were analyzed using multiple linear regression with the assistance of SPSS software. The findings indicate that the data met the classical assumption criteria, including normal distribution (Sig. = 0.200), absence of multicollinearity (Tolerance = 0.655; VIF = 1.527), and no evidence of heteroscedasticity. Simultaneous testing revealed that religious habituation and teacher role modeling jointly exerted a significant effect on students’ emotional intelligence (F = 45.558; Sig. = 0.000). Partially, religious habituation demonstrated a positive and statistically significant influence on emotional intelligence (β = 0.870; Sig. = 0.000), whereas teacher role modeling exhibited a positive but statistically non-significant effect (β = 0.220; Sig. = 0.053). The coefficient of determination (R² = 0.509) indicates that 50.9% of the variance in emotional intelligence is explained by the two independent variables.